Architecture and paleoenvironment of the fluvial gravel deposits of Las Cumbres formation (neogene), Mervil Village, La Rioja, NW-Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
A cut along the National Road 60, 400 m west of the Mervil Village, a small town located at the southern end of the "Bolsón de Pipanaco" (Pampean Ranges of NW-Argentina) unveils a 3-D fluvial and eolian architecture in beds that belong to the stratigraphic passage between the Salicas (Pliocene) and Las Cumbres (Plio- Pleistocene) Formations (Fig. 1 and 2). Fossil mammals found in the Salicas Formation belong to the Huayquerian fauna that could be dated in the Pliocene (Bossi et al., 1996). A four-fold classification of contacts hierarchy (Allen, 1983) was used to define individual sedimentary bodies and their associations: order 0, are the contacts between laminas within a laminaset; order 1 are the contacts between laminasets (represented by parallel or crossbedded cogenetic packages); order 2 contacts, cut order 1 contacts and embrace bedded packages or storeys, limited themselves by order 1 contacts, that show a similar genetic emplacement (similar features in outcrops); finally the order 3 contacts, cut and embrace sedimentary bodies limited by order 2 contacts, defining major groups or stages. Five distinct stages were recognized (Fig. 3): a lower A-S stage, covered by an extended floodplain F stage, cut deeply by the gravelly stage B, partially filled by L stage, and covered by the fluvial gravelly C stage at top (Fig. 4 and 5). The sandy A-S stage consists of channel and sandflat deposits formed by alternating fluvial (A) and eolian (S) storeys. Facies assemblage "A" is an association of 9 storeys (Fig. 3) composed of moderate sorted massive or cross-bedded sandstones, with few subrounded pebbles (schists and granites) in or near their concave bases. Most of the A storeys bottoms, are covered by a 1-5 cm thick silty shale drapes slightly disturbed or forming clay galls partially curled and/or removed (Fig. 4b and c). The facies assemblage S, is an association of 6 storeys (painted white in Fig. 5b and c) formed by well-sorted fine to medium size sandstones with occasional mud intraclasts (pebble sizes, not eolian materials probably incorporated by gravity collapse or sudden water sheets). The meter thick silty "F1" storey (Fig. 4 b and e) is composed of 10 to 11 tabular decimeter slightly indurated beds, interpreted as playa lake ("barreal") deposits by comparison with very similar sediments that fill the nearby barreal "El Señor de la Peña" a typical endorheic depression. This "F1" horizon is the source of most irregular blocks found at the foot of the left margin bank cuts of the B stage. The F2 storey (Figs. 3 and 4b) is composed of 0.90 m tabular to lenticular coarse sandstone horizon crowded of calcretes and rhyzoconcretions defining a paleosol horizon. The F3 storey is also composed of massive to crossbedded ill-sorted pebble coarse sandstones. Both F2 and F3 storeys were deposited by sudden floodings not connected to visible channel locations. The F3 storey is not related with the F2 storey calcretization. There are six irregular and lenticular storeys in the "B" stage, defined by concave and convex stratification designs. These storeys could be considered mesoforms in the sense of Bridge (1985, 1993) of the macroform "B". A close correlation of the contacts shown in the two walls of the road cut associated with contact orientation measurements and paleocurrents, allowed to build models of the 3D situation in several evolution steps starting with storey B2 ending up in storey B6 (Figs. 6 a-c). The B channel stage is deeply incised on the F and A-S stages indicating a change of the equilibrium profile. The B stage itself, represented by storeys B5 and B6, were mapped beyond the road cut for an extension of 700 m (in N-S sense) yielding a map that shows a NE-trending low sinuosity river with cut banks, lateral bar deposits, overbank deposits deposits with variable width.The last block (Fig. 6d) shows the abandon "L" stage of lacustrine fillings (see Fig. 3 for stratigraphy relations and Fig. 4 for details), composed of at least four storeys, three of them (L1, L2 and L3) are fillings of the central part of the pond and a fourth (L4) a clinoform, is a lateral deposit. The stage C outcrops at the top of the wall cuts covering through a third order contact, the stages F, L and B. It is composed of fine to medium size fluvial gravels without visible bank cuts. The very limited lateral and vertical exposures preclude it, from a further discussion.Most paleocurrent measurements were taken in the axis of concave structures (crossbeddings) and the points where the order 2 contacts merge into the basal order 3 contact. The point of merging of the order 2 and 3 contacts in convex stratified bodies, indicates the position of the bar structure, the paleocurrents at their bases show the local direction of the bar slope in this particular stage of growing (Fig. 7). Converging or diverging paleocurrent patterns at the outcrop face combined with vertical textural variations, unveil the position of the outcrop cut in relation to the hidden 3D structure. Most of the mapped architectural features yielded also paleocurrents measurements on cross-bedding and pebble imbrications that were integrated with the textural and structural evidences (Fig. 9). The scheme of Fig. 7 was used in the model of Fig. 9 to position the bar designs on the plan. The model of Fig. 9b, is a cartoon of a slightly ondulate landscape crossed from SSW to NNE by the B stage river channel. Fig. 8 shows the successive bank cuts created by the B stage channel during its migration to west. Calcretes and rhizoconcretions over convex or tabular gravels storeys, mapped as inside features of channel "B", indicate an ephemeral regime with riparian vegetation (Fig. 9). The Pituil River (Fig. 10) draining the northwest end of the Velasco Range and the sandy plains located north of the Mazán Range and near the center of the "Bolsón de Pipanaco'' were used as modern analogs of the ancient Mervil channel system (stages B and A-S respectively). The structural details shown by the Salicas Formation at the Mervil area around the road cut, are also present in the modern analogs, indicating a similar arid climate.
Keywords: Fluvial sedimentology; Pampean Ranges; Aluvial architecture; Neogene; Paleoenvironment